Clinical outcome of patients with recurrent or refractory localized Ewing's sarcoma family of tumors: A retrospective report from the Japan Ewing Sarcoma Study Group. Issue 3 (16th January 2021) - Umeda, Katsutsugu; Miyamura, Takako; Yamada, Kenji; Sano, Hideki; Hosono, Ako; Sumi, Minako; Okita, Hajime; Kumamoto, Tadashi; Kawai, Akira; Hirayama, Junya; Jyoko, Ryoji; Sawada, Akihisa; et al.
Abstract: Background: Patients with Ewing's sarcoma family of tumors (ESFT) who experience relapse or progression have a poor prognosis. Aim: This study aimed to identify the prognostic and therapeutic factors affecting overall survival (OS) of patients with recurrent or refractory localized ESFT. Methods and results: Thirty‐eight patients with localized ESFT who experienced first relapse or progression between 2000 and 2018 were retrospectively reviewed. The 5‐year OS rate of the entire cohort was 48.3% (95% confidence interval, 29.9%‐64.5%). Multivariate analysis of OS identified time to relapse or progression, but not stem cell transplantation (SCT), as the sole independent risk factor (hazard ratio, 35.8; P = .002). Among 31 patients who received salvage chemotherapy before local treatment, 21 received chemotherapy regimens that are not conventionally used for newly diagnosed ESFT. The objective response rate to first‐line salvage chemotherapy was 55.2% in the 29 evaluable patients. Time to relapse or progression was significantly associated with response to first‐line salvage chemotherapy ( P = .006). Conclusions: The present study fails to demonstrate significant clinical benefit of SCT for recurrent or refractory localized ESFT. Recently established chemotherapy regimens may increase the survival rate of patients with recurrent or refractory localized ESFT while attenuating the beneficial effect of SCT.